1977
DOI: 10.1037/0012-1649.13.5.460
|View full text |Cite
|
Sign up to set email alerts
|

The reliability, validity, and design of the Defining Issues Test.

Abstract: The Defining Issues Test, developed by Rest, was given to 365 subjects in three age groups, junior high (n =60,meanage= 13.9 years); high school (n = 200, mean age = 17.3); and college (n = 105, mean age = 20.2). The main findings of Rest and his associates were replicated. Each scale score discriminated significantly among age groups (p < .01), as did the Principled Reasoning (P) score. The validity of the P-score with respect to age group was estimated to be .48, and its reliability was estimated to be .70. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…The result of these modifications was a more equal representation of the various moral stages among the issues, which, in Rest's (Note 2) original test, were biased in frequency toward the conventional and principled levels (as has also been noted by Martin, Shafto, & VanDeinse, 1977).…”
Section: Methodsmentioning
confidence: 90%
“…The result of these modifications was a more equal representation of the various moral stages among the issues, which, in Rest's (Note 2) original test, were biased in frequency toward the conventional and principled levels (as has also been noted by Martin, Shafto, & VanDeinse, 1977).…”
Section: Methodsmentioning
confidence: 90%
“…In short, the cohortsequential analysis supports the cross-sectional data and the longitudinal data in suggesting that there is ontogenetic change on DIT P scores.7 Table 11 presents the design for what Schaie calls a "time-sequential" analysis, in which age and time of testing are the two factors. These are essentially three cross-sectional studies reported previously as unifactorial analyses by Martin et al (1977), Rest 6 Since the age factor was based on longitudinal data, a repeated-measures procedure was utilized on this factor but not on the cohort factor (see Baltes & Nesselroade 1972, p. 247). See Rest (1975) for details on sample and testing procedures.…”
Section: Recognizing These Problems In Cross-sectional and Longitudinmentioning
confidence: 99%
“…As previously mentioned, numerous early validation studies failed to control for variance in moral development scores that could be attributed to education and IQ (Martin, Shaftro, & Van Deinse, 1977). Since these studies, researchers have found a significant association between moral development scores and IQ (Dawson, 2002;Taylor, 1978).…”
Section: Kohlberg's Model Of Moral Developmentmentioning
confidence: 95%